Molecular hydrogen attenuates hypoxia/reoxygenation injury of intrahepatic cholangiocytes by activating Nrf2 expression. Issue 3 (4th November 2015) - Yu, Jianhua; Zhang, Weiguang; Zhang, Rongguo; Jiang, Guixing; Tang, Haijun; Ruan, Xinxian; Ren, Peitu; Lu, Baochun
Highlights H2 ameliorates cholangiocytes H/R injury in vitro. Nrf2 signaling is activated in cholangiocytes after exposed to H2. H2 could not protect Nrf2-silenced cholangiocytes from H/R injury. H2 protects cholangiocytes from I/R injury through in vivo.